Pengaruh Penanaman Modal Asing (PMA), Penanaman Modal Dalam Negeri (PMDN), dan Laju Inflasi Terhadap Pertumbuhan Ekonomi Kabupaten dan Kota di Provinsi Jawa Barat - Gayatri Dewata Adi Putri, (2022)
To achieve maximum economic growth, it is necessary to encourage the appliation of investment, as one form of investment is Foreign Investment and Domestic Investment. Apart from the influence of investment, inflation also has an important role in shaping economic growth. These three indicators will help create economic growth with the effectiveness of producing capital goods, import substitution components, finished goods, or semi-finished goods that are used to create business opportunities, and create jobs. In this study, it is intended to examine the effect of FDI, DDI, and inflation on economic growth that occurs in districts/cities in West Java Province. By using samples and populations from 16 regencies/cities in West Java Province in 2011-2020, sourced from BPS and BKPM West Java Province. This research uses multiple regression method using quantitative analysis. The result of the research is that the PMA variable has influence effect on economic growth, the PMDN, and Inflation variables have an influence on the economic growth of the Regency/City in West Java Province. Keywords: Economic Growth, FDI, DDI, Inflation rate